Phraseological units as a way of comic in the art texts (based on the works of children’s writers of the XIX - early XX centuries) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article considers the methods and techniques for using the phraseology as a means of creating a comic  in works of art for children.
Keywords: phraseology; language tools for creating the comic; the aesthetic function